BEAUTIFYING MOSQUES, ENHANCING WORSHIP: THE FIQH PERSPECTIVE OF FOUR MADHHABS AND MUHAMMAD IQBAL'S AESTHETIC CONCEPT - Mohamad Zakky Ubaid Ermawan; Ahmad Khudori Soleh; Mohammad Fadil Akbar Islamy (Al'Adalah, 2023)
Muslims recognize the significance of mosques as sites of worship and as centers for their religious and other activities. Various efforts are organized and designed to make mosques relevant to cultural changes and the needs of Muslims. Mosque buildings are often not identical in each region and nation, with different customs and cultures, and are sometimes even similar to other religions. In addition, the temptation of capitalism also raises questions about mosque designs that are overly grand and problematic for the socio-economic life of the community. This article aims to interrogate whether such a well-built mosque is permissible from the perspective of scholars of the four madhhabs of fiqh and the aesthetics of Muhammad Iqbal. Thus, this research uses descriptive-interpretive and textual methods to scrutinize fiqh views and analyze Iqbal's aesthetic perspective on the mosque building. The study revealed that the four madhhabs allow decorations on mosque buildings so that the mosque remains the principal place of worship and does not inconvenience the solemnity of the congregation's prayers. Furthermore, the mosque's decoration, ornamentation, design, and construction must provide meaningful objectives with practical usefulness and philosophical value; otherwise, for Iqbal, decorating a mosque in excess is wasteful and unavailing, and embellishing a mosque means squandering time and money.